SEXTORTION: PEMERASAN SEKSUA L DAN RELASI KEKUASAAN INTERNET PREDATORS DALAM MODUS KORUPSI BARU - Dewi, Seroja Kususma; Rini Diah Puri Handayani; Saputro, Dahvit Danang Adi (SERUNAI, 2023)
Sextortion is sexual violence on the Internet, where the perpetrator first blackmails the victim materially or sexually, and at the same time threatens the victim by spreading pornographic content. Usually, the perpetrator obtains pornographic content from the victim by tricking or threatening the victim and using coding methods. Sextortion is a form of crime that violates human rights and degrades women. Therefore, the author through qualitative methods and conceptual approach tried to provide new ideas related to efforts to minimise the act of sextortion and how the community could avoid the act of sextortion, namely by filling the legal vacuum and using the KCT method (Recognize, Prevent, Respond).